Canopy cover as the key factor for occurrence and species richness of subtropical stream green algae (Chlorophyta) - Peres, Cleto Kaveski; Tonetto, Aurélio Fajar [UNESP]; Garey, Michel Varajão; Branco, Ciro Cesar Zanini [UNESP] (Elsevier, 2017)
Understanding how local and regional environmental factors influence species richness remains a key issue in ecology. Green algae (Chlorophyta) are a diverse and widely occurring group, which may be a good model for studying the factors that influence species richness at local and regional scales. Here, we tested the influence of local (water quality and structural complexity) and regional environmental factors (phyto-ecological regions) on the occurrence and species richness of macroscopic green algae (MGA) in subtropical streams. We sampled algae in 105 streams located in the four major phyto-ecological regions of the Brazilian subtropics. We used cross-transect technique in streams to sample algae and environmental variables. To determine the most important variables in species occurrence and richness, we used Hierarchical Partitioning analysis (HP). We found that canopy cover alone explained 34% of MGA occurrence, regardless of phyto-ecological region. At the sites where MGA occurred, the species richness was determined by both regional and local factors. The species richness was mainly influenced by phyto-ecological region, which explained 34% of the variation in species richness, along with canopy cover and pH which explaining 22% and 15% respectively. The highest richness was found in non-forested regions, in transects without canopy cover, and slightly acidic pH. Our results illustrate how the combination of regional and local factors can shape the spatial distribution of species richness and are pivotal to understanding richness patterns at broad spatial scales.
Keywords: Benthic macroalgae; Brazilian streams; Phyto-ecological region; Shading